White Cerebellum Sign - Gopalakrishnan, Shridhar; Uddandam, Rajesh; Sodhi, Kirandeep (Journal of Nepal Paediatric Society, 2016)
The white cerebellum sign is an unusual but striking radiological sign of global hypoxia ischemia of the brain. Recognition helps in diagnosis and prognosis as this sign is usually associated with a uniformly poor outcome.